Factors affecting experiential satisfaction and behavioural intentions in urban tourism in Kuala Lumpur - Wong, Yong Shean (2019)
This study aims at examining the relationship between experiential quality, perceived equity, happiness, urban image, perceived value, experiential satisfaction and behavioural intentions for urban tourism in Kuala Lumpur. The data used in this study were based on a sample of 154 tourists that visited or currently visiting Kuala Lumpur. The results of this study shows that experiential quality, happiness, urban image and perceived equity positively affects experiential satisfactions, which in turn, positively affects behavioural intentions. The results of this study will help government of Malaysia, City Hall of Kuala Lumpur and tourism-related businesses in Kuala Lumpur to achieve their respective objectives.